Food intake evaluation in a group of elite track and field athletes - Vici, G.; Cesanelli, L.; Nalocca, M.; Belli, N.; Polzonetti, V. (Journal of Clinical & Diagnostic Research, 2019)
Introduction: Eating behaviours and nutritional status are key factors related to individuals` health. In athletes, diet optimisation has a key role in training adaptation achievement, injury prevention and good health status maintenance. However, nowadays it is still common to find diet behaviours not optimised with an increased risk of energy/nutrients deficiencies that can result not only in performance impairment but also in increased injury frequencies and malnutrition.